An approach to enhance aggregated source specific multicast scheme - Hassan Abdalla Hashim, Aisha; Hassan, Wan Hazlina; Arifin, Muaz Zainal; Ahmad, Ahmad Taqiyuddin; Al-Khateeb, Wajdi Fawzi Mohammed; Anwar, Farhat (Sunway University, 2008)
The Aggregated Source Specific Multicast (ASSM) scheme is proposed to overcome the limitations of Source Specific Multicast (SSM). It aims to handle the scalability issue of SSM. The key idea is that multiple groups are forced to share a single delivery tree. However, the ASSM scheme suffers from routers under utilization problem. In our previous work we have proposed an approach to overcome this problem. In this paper our proposed approach was presented and evaluated. It was shown that our proposed scheme results in achieving higher routers utilization.